Systematic Review: Effects of Residential Environmental Quality and Risks Acute Respiratory Tract Infections (ARI) - Is Fitiyarin Chamida; Onny Setiani; Budiyono Budiyono (Jurnal KESANS : Kesehatan dan Sains, 2026)
Introduction: Acute respiratory infection is one of the health problems that often occurs in the community, especially in residential environments with poor quality. Housing conditions that do not meet health requirements, such as inadequate ventilation, high occupancy density, poor lighting, and exposure to indoor air pollution, can increase the risk of respiratory infection. An unhealthy residential environment may facilitate the growth and spread of disease-causing microorganisms and affect the health of residents. Objective: To analyze the effect of residential environmental quality on the risk of acute respiratory infection. Methods: This study used a literature study method by examining several scientific articles discussing housing environmental conditions and the incidence of respiratory tract infection. Data were collected from relevant journals published between 2019 and 2024. Results and Discussion: Inadequate ventilation, high occupancy density, excessive humidity, poor lighting, and exposure to smoke and air pollution were the most common factors associated with respiratory infection. These conditions reduce indoor air quality and increase the possibility of disease transmission, especially among vulnerable groups such as children. Conclusion: Residential environmental quality affects the risk of acute respiratory infection. Improving housing conditions and environmental sanitation is necessary to reduce disease incidence and improve public health